Konstruksi Sosial Teknologi Media Baru pada Profesi Desainer Grafis Kelompok Digital Native - Utami, Athika Dwi Wiji; Trias Widha Andari (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2025)
This research examines how the social construction process occurs in the use of new media technology by the graphic designer profession. This technology study is in the context of social science, namely how the design profession interprets, responds, and adapts to the presence of technology that intersects with the profession. This research method is descriptive qualitative with selecting research informants using purposive sampling techniques. This research uses the perspective of a digital native graphic designer collected through observation and interviews. Technology exists to provide convenience for society, and society was also the first to create technology. Even though society seems to depend on technology, technology also depends on how society uses it. This is called a form of social construction of technology. Social construction also occurs in the use of technology by graphic designers which is a form of social process or social constructivism, the needs of the social environment which can influence the discovery of new technology, as well as technology that quickly adapts and continues to innovate. meet society's demands. Innovation from the social construction of technology in the design world produces two blades that return to society or the social environment, who will choose to use technology in what way and how. Designers determine what technology will be used, according to their needs. The four components of SCoT theory found in this research include Interpretive Flexibility, The Relevant Social Group, Closure & Stabilization, and The Wider Context.